The Library Head’s Strategy to Increasing Students’ Reading Interest - Diana, Eka; Rohimah, Ainur; Rofiki, Moh. (Electronic Journal of Education, Social Economics and Technology, 2025)
The head of the library is someone who has a high responsibility or leadership role in managing the library in the school. The purpose of this study is to analyse the strategies that have been applied by the head of the library in increasing students' interest in reading. High reading interest is one of the main keys in improving the quality of educational institutions, so there needs to be an active role of the school library. The research method used is a qualitative approach with a case study type. The research location is Nurul Jadid Junior High School, which is based on the school's efforts in developing a culture of reading literacy with various programmes supported by the library. Data collection in this study was carried out through observation, in-depth interviews with the head of the library, two teachers, and documentation related to the reading literacy program. Then the data analysis techniques used were data reduction, data presentation, and conclusion drawing. Furthermore, the results of this study show that the strategies implemented by the head of the library include providing a collection of books that are in accordance with the needs of students, implementing reading literacy activities that are attractive to students, and collaborating with teachers in school library-based learning. So that the implementation of this strategy is proven to increase students' interest in reading at Nurul Jadid Junior High School.